Alterações metabólicas, eficiência da transmissão e danos promovidos pelo Barley yellow dwarf virus (BYDV-PAV) em cinco cultivares de trigo - Lanzarini, Ariane Claudete (2006)
The Barley yellow dwarf virus (BYDV) cause annually considerable damages in its hosts, mainly in wheat, barley and oats in all the producing countries of these cereals. With the objective to detect, to quantify and to study the effect of the BYDVPAV on the metabolism of the plants and to verify the eficiency in the transmission of the virus for three species of aphids (Rhopalosiphum padi, Sitobion avenae and Schizaphis graminum) in five cultivars of wheat (BRS 177, BRS 179, BRS 194, BRS Camboatá and BRS Angico), conducted an experiment (experiment I) in house green together to Embrapa-Trigo Passo Fundo/RS. Experiment II, also carried through in house green of the Embrapa-Trigo, had as objective to evaluate the damages promoted for the BYDV-PAV in the same cultivars of wheat of experiment I. the delineation was of blocks to three repetitions with parcels subdivided in four, being that each one was infested with one of the species of aphids previously displayed acquisition viral and, a sub-parcel remained exempt of aphids, as healthy control. Experiment II had similar delineation, varying only how much the number of sub-parcels, that in this in case had been two, one concomitantly received the three species from aphids and to another one remained exempt of the aphids, as healthy control. In experiment I, twelve days after the rank of the aphids, became the Elisa test in flag leaf and wheat stem to confirm the species of the present virus in the experiment and quantified the virus in these different parts of the plant. The soluble protein levels had been determined, the levels of total sugars and texts of chlorophyll to analyzed the effect of the virus on the metabolism of the five wheat cultivars. To damages for the BYDV-PAV in wheat, be determination from agronomics characteristics and the components of the income. The data of experiment had been submitted to the analysis of variance and the averages to the test of Tukey 5%. The results of experiment I had confirmed the transmission of the BYDV-PAV for the three species of aphids. In leaf wheat flag had it did not have significant difference in the viral concentration between cultivars and between the vectors. In stem, the vector most efficient was the R.padi, while S. avenae and S. graminum had not differed statistical between them. The protein texts had been bigger in the healthy plants in all to cultivars the texts of total sugars had been bigger in the infected plants. It had reduction in texts of chlorophyll in the infected plants of wheat in all cultivars. The experiment II, evidence significant damages in function of the viral infection in all the tested variable. The agronomics characteristics, the most affected it was the weight of dry material, that varied of 26.49% (BRS 177) to 52,67% (BRS 179). For height of plants reductions of 12.56% (BRS 177) had been observed 15,51% (BRS Camboatá). And to the income components, the total income of grains was affected, whose reduction varied of 34.17% (BRS Camboatá) to 60,81% (BRS 179). In the average number of tillers for plant, only to cultivars BRS 179 and BRS Angico had presented reductions of 17,80% and 24,34% respectively. The reduction of the average number of grains varied of 26.12% (BRS Camboatá) to 54,29% (BRS 179). Also reduction in the weight of a thousand grains occurred that varied of 16,88% by 38,44% in BRS Camboatá and BRS 194 cultivars respectively. All the results found reiterate that the BYDV more deserves detailed studies, in view of the caused damages on the wheat plants